The Influence of Customer Digital Engagement, Organizational Agility, and Strategic Alignment on Digital Business Performance in the Fintech Industry - Djunaedi, Djunaedi; Widyastuti, Niken; Anantadjaya, Samuel PD; Nawangwulan, Irma M; Kusnadi, Iwan Henri; Muarief, Fahrurozi (Yayasan Gema Bina Nusantara, 2026)
The fintech sector requires businesses to select suitable technological tools and develop operational methods that will enable them to conduct their digital business activities. The research study examines how customer digital interaction together with organizational agility and strategic alignment impacts the digital business results of the fintech sector. The research project uses a quantitative research approach together with an explanatory research framework. The researchers used purposive sampling methods to distribute questionnaires to 170 employees from various fintech companies. The researchers conducted data analysis through multiple linear regression after they completed validity testing and reliability testing together with classical assumption testing. The results show that customer digital engagement together with organizational agility and strategic alignment create positive effects on digital business performance within the fintech industry. Customer digital engagement enables customers to establish deeper connections with digital services while organizational agility allows companies to adjust their operations according to market conditions and strategic alignment ensures that business operations work in harmony with information technology to achieve maximum technology advantages. The research results enable fintech companies to achieve sustainable improvements in their digital business performance through practical results.